Action Of Homoeopathy In Chronic Diseases – A Retrospective Analysis (Advancements in Homeopathic Research, 2024)
Background: Homeopathy, as a holistic system of  medicine, plays a pivotal role in the management  of both acute and chronic diseases, offering a  potential for permanent cure without causing harm  to the patient. This retrospective analysis aims to  underscore the advantages of homeopathy, focusing  on common chronic ailments such as irritable bowel  syndrome (IBS), polycystic ovarian syndrome  (PCOD), bronchial asthma, allergic rhinitis, and low  backache. Materials and Methods: The study was conducted  retrospectively among patients attending the general  Outpatient Department (OPD 2) at the National  Homeopathy Research Institute in Mental Health,  Kottayam, Kerala, every Tuesday from January 2023  to July 2023 (7 months). Analysis of data from 1677  patients revealed patterns of frequently indicated  medicines. Results: A total of 1677 patients were included in  the study, revealing distinct patterns in demographics  and health conditions. The age distribution (Table  1, Figure1) indicated a higher prevalence among  individuals aged 51-60 years (24%), while those in  the 91-100 age group showed the least representation  (1%). Notably, a predominant male presence  was observed, constituting 51% of the patient  population(Table2, Figure2). Among the patients,  197 were new attendees, while 1480 were returning  patients, highlighting the sustained engagement of  individuals with homeopathic care over time (Table 3,  Figure3). The most prevalent disorders encountered  during the study period (Table4, Figure4) were  Bronchial Asthma (10%), Acid Peptic Disease (9%),  and Diabetes Mellitus (9%). The most frequently  used remedies were Sulphur, Pulsatilla, Nuxvomica,  and RhusToxicodendron. Conclusion: In summary, this retrospective study  involving 1677 patients at the National Homeopathy  Research Institute in Mental Health revealed a  predominant male demographic, with a concentration  of cases in the 51-60 age group. Common disorders  included Bronchial Asthma, Acid Peptic Disease,  and Diabetes Mellitus, while Sulphur, Pulsatilla,  Nuxvomica, and Rhustox emerged as frequently  indicated remedies. Notably, the study showcased a  remarkable improvement in all patients, affirming the  efficacy and significance of homeopathy in achieving  positive therapeutic outcomes.
Keywords: Homeopathy; Irritable Bowel Syndrome (IBS); Polycystic Ovarian Syndrome (PCOD); Bronchial Asthma; Allergic Rhinitis; Low Backache